PERCEPATAN PENYEDIAAN BIBIT JERUK KUOK (Citrus nobilis Lour) DENGAN METODE KULTUR EMBRIO - Mahadi, Imam (Jurnal Agroteknologi, 2026)
Kuok sweet oranges or Kuok oranges is derived from Siam oranges (Citrus nobilis Lour) is a local fruit Riau province crowded popular by the public. This fruit provides a promising business opportunity, however the limited availability of seedlings will need to be managed for the assessment of getting ready-to-be seeds available. Therefore, this study aims to determine the effect of IAA and Giberellin on the growth of embryo culture of Kuok oranges (Citrus nobilis Lour). This research uses Factorial Random Design. For the first factor Mikropropagasi IAA (I) consisted of 0 mgl-1 - 3 mgl-1 and the second actor Giberellin (G) consisted of 0 mgl-1 -4 mgl-1. The parameters measured were the time of shoots, the percentage of live eksplan, the time of the root, the number of shoots, the number of roots, and the shoot height. Data were analyzed using ANOVA and tested further with DNMRT at 5%. The results showed that the combination of IAA and Giberellin significantly affected the growth of plantlets from Kuok sweet organge embryos. The I2G3 treatment (2 mgL-1 IAA and 2 mgL-1 Giberellin) was the best for the average shoot growth time of the fastest 5,67 days after culture, 100% plantlet survival percentage, the average number of shoots was 5.83, the average shoot height was 10.67 cm, average root growth 7.83 days after culture and the average number of roots was 5.33. The plantlets from this study can be used as a source of germplasm for Kuok sweet orange seeds.